INTERNET COMMUNICATION IN THE PROJECTION OF TRANSFORMATION OF COGNITIVE SIDES OF VIRTUAL PERSONALITY - Kenenbaev, ErkinToylibaevich (Mental Enlightenment Scientific-Methodological Journal, 2025)
The anonymity inherent in online communication, especially in combination with the physical distance of participants, can provoke non-standard and, at times, deviant behavior. In this article, we examine the specifics of such behavior in the online environment, and also raise topical issues of self-identification of users who act as linguistic personalities in the virtual space of the Internet. This study is aimed at identifying the fundamental factors that determine changes in language caused by the restructuring of text tools and communication channels in an environment of anonymity and distance. As a result, there is an active stylistic assimilation of the latest text formats and a rapid development of organized colloquial speech, which affects all levels of language, including online vocabulary, specialized electronic slang, the genre of electronic letters and the use of language manipulation technologies.